2009
DOI: 10.1016/j.jtcvs.2009.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Surgical risk of preoperative malperfusion in acute type A aortic dissection

Abstract: Preoperative malperfusion is a significant risk factor influencing perioperative and long-term survival after surgery for acute type A dissection. Percutaneous interventional procedures and delayed surgery should be considered in patients with clinically apparent mesenteric malperfusion because of the dismal prognosis of immediate surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 32 publications
8
141
0
4
Order By: Relevance
“…Several recent reports highlight the crucial role of preoperative malperfusion and ischaemia, localized or generalized as in shock, as predictors of adverse surgical outcome [9][10][11][12] . Specifically, the Penn classification of acute aortic dissection, based on preoperative ischaemic conditions, has recently been described 13,18 .…”
Section: Abstract Type a Dissection -Stanford Classification -Debakeymentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reports highlight the crucial role of preoperative malperfusion and ischaemia, localized or generalized as in shock, as predictors of adverse surgical outcome [9][10][11][12] . Specifically, the Penn classification of acute aortic dissection, based on preoperative ischaemic conditions, has recently been described 13,18 .…”
Section: Abstract Type a Dissection -Stanford Classification -Debakeymentioning
confidence: 99%
“…were Penn class Aa (absence of branch vessel malperfusion or circulatory collapse), 11 (19%) Penn class Ab and outcomes [10][11][12] . Two main single-centre studies have evaluated the validity of the Penn classification.…”
Section: According To Penn Classification 28 Patients (48%)mentioning
confidence: 99%
“…A recent study of the IRAD ( International Registry of Acute Dissection) database showed that mortality exceeded 95% when treatment of type A dissection is undertaken without initial treatment of visceral malperfusion [7]. Therefore, some authors have recommended performing simultaneous mesenteric revascularization procedure and central aortic repair to prevent intestinal infarction resulting from the long duration of ischaemia incurred while repairing the type A dissection [8]. …”
Section: Visceral Malperfusion From Aortic Dissection and Spontaneousmentioning
confidence: 99%
“…Despite its reported improved outcomes, the hemiarch approach is still associated with around 50% persistent distal FL patency (22). In the acute phase this can induce distal organ malperfusion due to static or dynamic obstruction of aortic branch vessels (23,24). Importantly, the manifestation of ischemia in some territories such as the bowel can be quite subtle, right until they advance to the irreversible stage (21).…”
Section: Current Concepts In Ataadmentioning
confidence: 99%